2008
DOI: 10.1007/s12185-008-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Nasal NK/T-cell lymphoma: epidemiology and pathogenesis

Abstract: Nasal NK/T-cell lymphoma (NKTCL) is an uncommon disease, but usually shows a highly aggressive clinical course. The disease is much more frequent in Asian and Latin American countries than in Western countries, and is universally associated with Epstein–Barr virus (EBV) infection. Analyses of gene mutations, especially p53 and c-KIT, revealed the different frequencies by district. Epidemiological studies revealed the changes of the disease frequency in Korea during the period from 1977–1989 to 1990–1996. Case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 65 publications
3
115
0
1
Order By: Relevance
“…In parallel, investigators have identified genetic features that may be important in this disease. For example, a low frequency of the HLA-A*0201 allele was reported in patients with ENKTL by Japanese investigators (Kanno et al, 2000;Au et al, 2004;Aozasa et al, 2008). Furthermore, Au et al (2005b) showed that the prevalence of ENKTL in Chinese immigrants to North America remained higher than in the background population, but lower than in Hong Kong Chinese.…”
Section: Racial Patterns Of Nk/t Cell Lymphoma ª 2011 Blackwell Publimentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, investigators have identified genetic features that may be important in this disease. For example, a low frequency of the HLA-A*0201 allele was reported in patients with ENKTL by Japanese investigators (Kanno et al, 2000;Au et al, 2004;Aozasa et al, 2008). Furthermore, Au et al (2005b) showed that the prevalence of ENKTL in Chinese immigrants to North America remained higher than in the background population, but lower than in Hong Kong Chinese.…”
Section: Racial Patterns Of Nk/t Cell Lymphoma ª 2011 Blackwell Publimentioning
confidence: 99%
“…These observations suggest that EBV infection is directly involved in the development of ENKTL. Additionally, recent studies suggest that lifestyle factors and environmental exposures, such as occupational exposure to pesticides and solvents, may be risk factors for the disease (Au et al, 2004;Aozasa et al, 2008). In parallel, investigators have identified genetic features that may be important in this disease.…”
Section: Racial Patterns Of Nk/t Cell Lymphoma ª 2011 Blackwell Publimentioning
confidence: 99%
“…T-cell receptor-g and immunoglobulin H (Framework region (Fr)1, Fr2 and Fr3]) loci were in the germinal conformation. Cytogenetical analysis disclosed a near tetraploid pattern with a complex formula with numerous numerical and structural chromosome changes as follows: 50-82, ÀXx4 [13],À3 [12], add(3)(p?24) [3], À4 [12], À5 [12], del(6)(q12) [2], þ del(6)(q12) [11], add(6)(q26) [11], del(7)(p1?2p1?5) [9], add(7)(p1?2) [7], À7 [4], À8, À8 [12], À9 [3], À9, À9 [10], À10, À10 [13], À11 [13], add(11)(p11) [4], þ add(11)(p11) [8], add(11)(q22) [10], þ add(11) (q22) [2], À12 [9], À13 [11], À14 [3], À15 [4], À16, [3], À17 [4], À17, À17 [8], add(18)(p11) Â 2 [13], þ 20 [3], þ mar1 [12], þ 1-7mars [11] cp [13]. As some structural abnormalities are present in duplicate, they occurred before endoreduplication, probably as some numerical one, whereas some others obviously occurred as secondary events (Figure 2b).…”
Section: Mec04 Nk Cell Line Characteristicsmentioning
confidence: 99%
“…5 Few putative oncogenic mechanisms were reported. These involve mutations of genes regulating apoptosis such as Fas and p53, [6][7][8][9][10] as well as expression of P-glycoproteins. 11 Moreover, a low expression level of the granzyme B protease inhibitor 9 was associated with a worse prognosis and cell dedifferentiation, suggesting a role for this protein in the pathophysiology of these malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…En la mayor parte de los casos publicados el VEB es detectado en las células tumorales mediante hibridación in situ, siendo de ayuda diagnóstica. También se identifica en sangre en 70% de casos [6]. El diagnóstico de esta entidad se basa en los datos clínicos y sobre todo en los hallazgos histopatológicos e inmunofenotípicos mencionados.…”
Section: Descripciónunclassified